The Effect of Self-Regulated Learning Toward Students’ Academic Stress in Malang - Miftahul Hamim; Yuli Rahmawati (Universitas Muhammadiyah Enrekang, 2022)
Health mental is a crucial factor for student which needs attention in the process of teaching and learning. Moreover, the pandemic of Covid-19 has shifted the process of teaching and learning into online learning. Undeniably, that condition has pushed students to have more activities of independent learning or self-regulated learning. This research investigates the effect of self-regulated learning toward students’ academic stress in Malang. There were 99 students coming from 19 Universities in Malang who participate as the subject of this study. The quantitative method was used in this study. To collect the data, survey was done in the form of online questionnaire consisting of several questions. The Likert scale was used to gain the score of each question. The result shows that self -regulated learning does not affect too much on students’ academic stress. The data resulted from the questionnaire from 100 respondents show only 27% of correlation. This matter is caused by another influential aspects such as the lack motivation of the students, time management, and unsupportive relation of people around. Based on three aspects which become the focus in self-regulated learning, the respondents were quite good in doing metacognition by utilizing to-do list in learning. However, they also show that the learning and teaching condition is less supportive to gain more achievement which drives students to have lack of motivation. The habit of respondents also show that they tend to solve the problem on their own which bring them into their academic stress. Furthermore, their time management and unsupportive environment can also be the trigger of academic stress.